Characterization of RDX and HMX explosive adduct ions using ESI FT‐ICR MS. (6th August 2020) - Lee, Jihyeon; Kim, Min Sun; Kim, Hyun Sik; Choe, Yoong‐Kee; Cho, Soo Gyeong; Goh, Eun Mee; Kim, Jeongkwon
Abstract: Investigation of two common explosives such as cyclonite (RDX) and cyclotetramethylenetetranitramine (HMX) using a mass spectrometer with ultrahigh resolution and accuracy has not been comprehensively performed. Here, ultrahigh mass accuracy 15‐T Fourier transform–ion cyclotron resonance mass spectrometry (FT‐ICR MS) spectra were utilized to comprehensively characterize the adduct ions of RDX and HMX. Two different ionization sources such as a conventional electrospray ionization (ESI) source and a chip‐based static nano‐ESI source were used to investigate the adduct ions of RDX and HMX. The ESI‐MS analyses of two explosives in negative ion mode provide some adduct ions of RDX and HMX even without prior addition of their corresponding anions. A total of six types of adduct ion were characterized: [M + Cl] −, [M + HCOO] −, [M + NO2 ] −, [M + CH3 COO] −, [M + NO3 ] −, and [M + C3 H5 O3 ] −, where M is either RDX or HMX. The ultrahigh accuracy of the 15‐T FT‐ICR MS was utilized to distinguish two closely spaced peaks representing the monoisotopic [M + NO2 ] − and second isotopic [M + HCOO] − ions, thereby enabling the discovery of a [M + NO2 ] − adduct ion in the ESI analysis of RDX or HMX. [M + NO2 ] − and [M + CH3 COO] − adduct ions were only observed when using a static nano‐ESI source. It is the first report explaining the discovery of [M + NO2 ] − adduct ion in the ESI‐MS analyses of RDX and HMX.